Effect of magnetic field on germination of chickpea (Cicer arietinum L.) - ghadrieh mahmoudi; Ali ghanbari; Mahdi rastgoo; mostafa gholi zade; iraj tahmasebi (پژوهش‌های حبوبات ایران, 2016)
Introduction Proteins are one of the basic and essential required compounds for life, and the creatures receive it either from a plant or animal origin. It has been reported that the positive effects caused by applying the magnetic field are due to the paramagnetic properties of the cells within the plant, and pigments such as the Chloroplast. Biophysical methods (magnetic fields, electricity, etc.) could improve the growth of plants with high energy rates. These methods, improve the energy levels independent from their source, and increase the electric potential of the cell membrane. Stimulating physical methods do not affect the physiological traits of the plant controlled by the genetic systems. In order to study the effect of intensity and duration of magnetic field on some properties of seed germination of chickpea (Cicer arietinum L.) cultivar ILC482 an experiment was conducted in Advanced Research Laboratory of Ferdowsi University of Mashhad, Iran. The goal of the experiment was to determine the possibility of improving the germination and vigor of the chickpea seed by using various intensities and durations of a magnetic field.